Abuso de Autoridad de la Fuerza Pública Municipal en contra del Vendedor Ambulante - Armijos Sáenz, Yessenia Elizabeth (2017)
Research in this thesis is based on abuse of authority exists by the municipal police against the peddler when executing the persecution and confiscation of products and tools which is prohibited by the Constitution of the Republic of Ecuador, abuse of authority in law, means to misuse or arbitrary use of authority, the action of a despotic power; in short, any act that went outside the limits imposed by reason, justice, attack directly or indirectly law or the general interest, these attitudes by municipal violate constitutional provisions. One of the violated rights performance is freely chosen which is guaranteed by the Constitution of the Republic of Ecuador but this is not respected by the abuse of authority exercised by local police against street vendors. When applying the polls the same as they were led to street vendors could see that their rights are violated in different ways so I consider it necessary that in the Organic Code of Territorial Organization Autonomy and Decentralisation reforms continue to be punished the municipal police persecution and confiscamiento of products and tools exerted against the peddler, so it must be implemented a sanction for administrative authority that incites perform such acts because they are prejudicial to work freely chosen under that this type of job performance is guaranteed by the Constitution and international treaties and agreements.